PENGARUH STRUKTUR MODAL DAN KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN SEKTOR PERTAMBANGAN - Annisa Fitri Wahono, - (2019)
This research was conducted to test the influence of capital structure and financial performance on firm value in the mining sector. Research variabels consist of capital structure, financial performance, and firm value. Doing research on the 42 company's which listed on the Indonesia Stock Exchange in 2014-2017 as a population. The samples of the study were 17 companies chosen by purposive sampling method.. Data analysis is done using the Microsoft Excel 2010 and hypothesis testing in this study using a Panel Data Regression Analysis with the program E-Views 9.0 and the level of significance of 5% (0,05). The results of this study proved that: (1) capital structure that represented by DER has no effect on firm value, (2) profitability that represented by ROE has significant positive effect on firm value, and (3) liquidity that represented by CR has no effect on the firm value.